Design and Synthesis of Small Molecules as Potent Staphylococcus aureus Sortase A Inhibitors - Min Woo Ha; Sung Wook Yi; Seung-Mann Paek (MDPI AG, 2020)
The widespread and uncontrollable emergence of antibiotic-resistant bacteria, especially methicillin-resistant Staphylococcus aureus, has promoted a wave of efforts to discover a new generation of antibiotics that prevent or treat bacterial infections neither as bactericides nor bacteriostats. Due to its crucial role in virulence and its nonessentiality in bacterial survival, sortase A has been considered as a great target for new antibiotics. Sortase A inhibitors have emerged as promising alternative antivirulence agents against bacteria. Herein, the structural and preparative aspects of some small synthetic organic compounds that block the pathogenic action of sortase A have been described.